1990
DOI: 10.1038/bjc.1990.97
|View full text |Cite
|
Sign up to set email alerts
|

How frequent is spontaneous remission of neuroblastomas? Implications for screening

Abstract: Summary The 'true' incidence of spontaneous regression of neuroblastomas is uncertain. However, the frequency of spontaneous regression is important when the benefits of screening procedures are considered. In the population-based Danish neuroblastoma survey 1943-80, spontaneous regression was documented in less than 2% of cases. However, the 'true' incidence may be higher. The epidemiological findings of increased incidence and survival rates with an unchanged mortality rate may suggest the inclusion of borde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 38 publications
(60 reference statements)
1
25
0
2
Order By: Relevance
“…Neuroblastoma is a unique malignancy which includes the highest proportion of cases that will spontaneously regress compared to any other human cancer, 28,29 but the majority of patients have a relentless malignant disease that is difficult to cure even with intensive chemoradiotherapy. 1 Our data suggest that the chromosome 6p22 risk alleles not only influence the likelihood of developing neuroblastoma, but also the likelihood for developing a more malignant phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroblastoma is a unique malignancy which includes the highest proportion of cases that will spontaneously regress compared to any other human cancer, 28,29 but the majority of patients have a relentless malignant disease that is difficult to cure even with intensive chemoradiotherapy. 1 Our data suggest that the chromosome 6p22 risk alleles not only influence the likelihood of developing neuroblastoma, but also the likelihood for developing a more malignant phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…1992), and extensive data have been published for Japan (Hanawa et al, 1990 (Sawada et al, 1984(Sawada et al, . 1986 (Carlsen. 1990: Goodman.…”
mentioning
confidence: 99%
“…However, several data suggested that an antitumor response was occasionally induced in patients and that spontaneous remission was observed even in advanced cases. 7 Those findings prompt us to consider that an immune therapy can be applicable to neuroblastoma patients.…”
Section: Nduction Of Effective Antitumor Immunity In Tumor-mentioning
confidence: 99%